Rheology of Biopolymer Solutions and Gels - David R. Picout; Simon B. Ross-Murphy (The Scientific World Journal)
Rheological techniques and methods have been employed for many decades in the characterization of polymers. Originally developed and used on synthetic polymers, rheology has then found much interest in the field of natural (bio) polymers. This review concentrates on introducing the fundamentals of rheology and on discussing the rheological aspects and properties of the two major classes of biopolymers: polysaccharides and proteins. An overview of both their solution properties (dilute to semi-dilute) and gel properties is described.